Design considerations of a multitasked electric machine for automotive applications - Mese, Erkan; Ayaz, Murat; Tezcan, M. Murat (ELSEVIER SCIENCE SA, 2016)
This paper introduces a new electric machine for Front-End Accessory Drive (FEAD) of Hybrid Electric Vehicles (HEVs). The novelty of the electric machine lies in its ability to perform multitasking. Besides the independent motor or independent generator operation like any other electric machine, the proposed machine is able to run as motor and generator simultaneously. A dual winding electric machine forms the core part of the proposed system. Windings of the electric machine are concentrated type so that electrical and magnetic isolation is maintained. This allows simultaneous motoring and generating operation in the single housing of electric machine. Design considerations of the proposed electric machine have been outlined in the paper. Comparison between proposed and conventional approaches has been made to highlight potential benefits of the new approach. Thermal analyses have been performed to show the suitability and limits of the multitasked electric machine in the HEV applications. Overall performance of the proposed machine is presented by experimental results. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Permanent magnet synchronous machine (PMSM); Concentrated winding; Magnetic decoupling; Dual winding PM machine (DWPMSM); Fault tolerant operation; Hybrid electrical vehicle applications; COGGING TORQUE; MOTORS; Engineering